2017
DOI: 10.3390/min7100180
|View full text |Cite
|
Sign up to set email alerts
|

Heap Leaching of Caliche Ore. Modeling of a Multicomponent System with Particle Size Distribution

Abstract: Abstract:Caliche is a mineral exploited in northern Chile, from which iodine and Nitrate salts (saltpeter) are obtained. This ore is the most important source of iodine in the world and is processed mainly by heap leaching using water as a leaching agent. Heap leaching of caliche ore is carried out by the stacking of ROM (Run-Of-Mine) material, where the particle size distribution covers a wide range, from a few millimeters up to several decimeters, even diameters about 1 m. During the leaching, the multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Another example of repurposing is the use of the reject brine of desalination process in mineral processing. Studies have shown that the leaching of caliche using reject brine is technically feasible and delivers similar results than using seawater (Ordóñez et al 2015(Ordóñez et al , 2017. In another study, the use of reject brine in the leaching of pure chalcocite provides better results than the use of seawater (Torres et al 2020).…”
Section: Repurpose (R6)mentioning
confidence: 99%
“…Another example of repurposing is the use of the reject brine of desalination process in mineral processing. Studies have shown that the leaching of caliche using reject brine is technically feasible and delivers similar results than using seawater (Ordóñez et al 2015(Ordóñez et al , 2017. In another study, the use of reject brine in the leaching of pure chalcocite provides better results than the use of seawater (Torres et al 2020).…”
Section: Repurpose (R6)mentioning
confidence: 99%
“…Around 20% of the world's copper production is obtained by heap leaching. This process has been modeled by many authors; however, the validation, verification and implementation of these models are difficult since there is uncertainty about the operating conditions and parameters of the leaching model [24][25][26].…”
Section: Mathematical Modeling Of Heap Leachingmentioning
confidence: 99%
“…In addition to copper oxides, heap leaching is applied to a wide range of minerals, including copper sulphide minerals, such as chalcocite [5][6][7], covelline [8][9][10], or chalcopyrite [11][12][13]. On the other Materials 2023, 16, 3812 2 of 23 hand, non-metallic minerals, such as saltpeter, can also undergo leaching processes [14,15]. Applications of leaching in such cases have been studied by various authors [16][17][18] who have modeled mineral leaching at both laboratory and industrial scales.…”
Section: Introductionmentioning
confidence: 99%